Powder’s Trauma in Netflix TV Series Arcane (2021) - Khosyi, Vian Abdillah (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
Trauma is a mental wound that occurs after experiencing a traumatic incident. This study is focused on Powder from Netflix animated TV Series Arcane (2021) written by Christian Linke and Alex Yee, who has the depiction of trauma after a traumatic incident that involved the death of her loved ones. The researcher uses the theory of trauma by Cathy Caruth (1996) to see the main cause and manifestation of trauma in Powder’s life. The methodology that will be used for this research is in the form of qualitative content analysis, where the researcher will examine the animated TV series Arcane (2021) by Christian Linke and Alex Yee on Netflix by using the visual elements expressed in the TV series, alongside the textual data provided from the series’ subtitles. The results of the study found out that Powder’s manifestation of trauma comes in the form of hallucination and nightmares where she would remember the death of her loved ones.